2013
DOI: 10.2741/s391
|View full text |Cite
|
Sign up to set email alerts
|

The role of natural killer cells in pulmonary immunosurveillance

Abstract: Natural killer (NK) cells were originally identified as lymphocytes capable of killing cancer cells without prior sensitization (1). Further characterization of these cells in both humans and rodent models has expanded their role towards a broad-based immunosurveillance of diseased and healthy peripheral tissues. Among peripheral organs, the lung contains the largest percentage of NK cells. Accordingly, NK cells are implicated in many immunological responses within the lung, including innate effector functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…The lung contains the largest percentage of NK cells among the peripheral organs [14], and the postoperative period is known as the ‘decisive period,’ when NK cell-mediated immunity suppresses emerging lung cancer metastasis [15, 16]. Based on these assumptions, a previous study by Maher et al [8] reported that a group of 99 recurrent patients who underwent VATS lung cancer surgery had greater postoperative opioid use than the non-recurrent group.…”
Section: Discussionmentioning
confidence: 99%
“…The lung contains the largest percentage of NK cells among the peripheral organs [14], and the postoperative period is known as the ‘decisive period,’ when NK cell-mediated immunity suppresses emerging lung cancer metastasis [15, 16]. Based on these assumptions, a previous study by Maher et al [8] reported that a group of 99 recurrent patients who underwent VATS lung cancer surgery had greater postoperative opioid use than the non-recurrent group.…”
Section: Discussionmentioning
confidence: 99%
“…They then contribute to antiviral immunity by killing infected host cells, regulating T-cell function and secreting interferon (IFN-g) (Hesker & Krupnick, 2013). NK cells additionally contribute to clearance of pneumococcal infection through interaction with infected macrophages and dendritic cells (Elhaik-Goldman et al, 2011;Hesker & Krupnick, 2013;Mandelboim et al, 2001). Decreased numbers of NK cells in the lung and impaired NK cell function after influenza infection of mice have been shown to impair innate responses against S. aureus infection by contributing to a lack of activation of AMs (Small et al, 2010).…”
Section: Alveolar Macrophages (Ams)mentioning
confidence: 99%
“…NK cells can recognize viral structures on infected cells and respond to stress signals released by the infected host. They then contribute to antiviral immunity by killing infected host cells, regulating T-cell function and secreting interferon (IFN-g) (Hesker & Krupnick, 2013). NK cells additionally contribute to clearance of pneumococcal infection through interaction with infected macrophages and dendritic cells (Elhaik-Goldman et al, 2011;Hesker & Krupnick, 2013;Mandelboim et al, 2001).…”
Section: Alveolar Macrophages (Ams)mentioning
confidence: 99%
“…Among peripheral tissues, the lung contains the largest percentage of NK cells, indicating potential crucial involvement of NK cells in respiratory infections (22). Indeed, NK cells have been implicated in early defense against several viral (respiratory syncytial virus [RSV] and influenza) and bacterial (Mycobacterium tuberculosis and Bordetella pertussis) pathogens that cause pneumonia (23)(24)(25). NK cells may participate in defense against respiratory pathogens via various mechanisms, including direct lysis of infected cells, production of chemokines that amplify the host's inflammatory response, production of antiviral cytokines, such as IFN-␥ and tumor necrosis factor alpha (TNF), and activation of DCs that mediate T cell differentiation and trafficking to the lung (23,26).…”
mentioning
confidence: 99%
“…Indeed, NK cells have been implicated in early defense against several viral (respiratory syncytial virus [RSV] and influenza) and bacterial (Mycobacterium tuberculosis and Bordetella pertussis) pathogens that cause pneumonia (23)(24)(25). NK cells may participate in defense against respiratory pathogens via various mechanisms, including direct lysis of infected cells, production of chemokines that amplify the host's inflammatory response, production of antiviral cytokines, such as IFN-␥ and tumor necrosis factor alpha (TNF), and activation of DCs that mediate T cell differentiation and trafficking to the lung (23,26). In some instances, particularly during more severe respiratory infections, NK cells can be responsible for acute lung immune injury and mortality (27)(28)(29).…”
mentioning
confidence: 99%